2008
DOI: 10.1111/j.1365-3156.2008.02040.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions for the prevention of HIV and other sexually transmitted infections in female sex workers in resource poor setting: a systematic review

Abstract: Summaryobjective To systematically review the evidence for effectiveness of HIV and sexually transmitted infection (STI) prevention interventions in female sex workers in resource poor settings.method Published and unpublished studies were identified through electronic databases (Cochrane database, Medline, Embase, and Web of Science), hand searching and contacting experts. Randomizedcontrolled-trials and quasi-experimental studies were included if they were conducted in female sex workers from low and middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
159
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(169 citation statements)
references
References 73 publications
9
159
1
Order By: Relevance
“…5 In a systematic review of the literature on HIV prevalence among vulnerable populations in Brazil, Malta et al 6 found that sex workers were three times more likely to use condoms with clients than with steady partners (67.3 versus 19.2%) 6 . This difference between condom use with clients and partners is consistent with the results of other studies conducted in Brazil [7][8][9] , and is a major trend in international research [10][11][12] . Only one survey specifically about the use of female condoms was found.…”
Section: Prevention Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…5 In a systematic review of the literature on HIV prevalence among vulnerable populations in Brazil, Malta et al 6 found that sex workers were three times more likely to use condoms with clients than with steady partners (67.3 versus 19.2%) 6 . This difference between condom use with clients and partners is consistent with the results of other studies conducted in Brazil [7][8][9] , and is a major trend in international research [10][11][12] . Only one survey specifically about the use of female condoms was found.…”
Section: Prevention Methodssupporting
confidence: 81%
“…REV BRAS EPIDEMIOL SEP 2015; 18 SUPPL 1: [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] prostitution has aspects that remain in Brazil's Penal Code. Although the inclusion of "sex workers" in the Brazilian Classification of Occupations by the Ministry of Labor ensures the right to social security and other labor benefits, commercial activities related to prostitution (such as brothels) are illegal, which creates an extremely difficult context for sex workers to work safely.…”
Section: Introductionmentioning
confidence: 99%
“…Empowerment of sex workers, starting with building awareness and recognition, is the key to establish longterm, sustainable changes to their health and wellbeing (Chattopadhyay & McKaig, 2004). Evidence suggests that intervention strategies that empower sex workers result in more success in both acceptability of the intervention as well as prevention of HIV transmission (Shahmanesh et al, 2008). However, the ramifications of these intervention strategies that target sex workers is unknown, such as the potential to impact stigma, violence, or drive sex work underground.…”
Section: Building An Enabling Environment and Reducing Violencementioning
confidence: 99%
“…Without such information, the size of the population being affected by STI may stay largely unknown as well as their health needs (Shahmanesh et al, 2008). An understanding of STI levels and its distribution across a geographical region would allow the planning of effective prevention efforts that correctly address the needs of most vulnerable groups (Dhawan & Khandpur, 2009;Jain et al, 2008).…”
Section: Resultsmentioning
confidence: 99%